Die Jugend des Dionysos Die Ampelos-Episode in den "Dionysiaka" des Nonnos von Panopolis - Kröll, Nicole (Millennium - Studien/Millennium Studies, 2016)
The Millennium Studies seek to transcend boundaries, boundaries between epochs and regional spaces, as well as boundaries between disciplines. Millennium is international, transdisciplinary and epoch-wide. The editorial board and the advisory board represent a broad spectrum of subjects: articles in art and literary criticism are just as right as historical, theological and philosophical contributions to the Latin and Greek cultures as well as to the oriental ones.